Encyclopedia of Criminology and Criminal Justice - Bruinsma, Gerben (SpringerLink Bücher, 2014)
The Encyclopedia consists of approximately 600 entries, organized alphabetically, covering these ten major areas: Corrections and Criminal Justice Supervision -- Courts, Sentencing and the Judicial System -- Crimes, Criminals and Victims -- Crime Places and Situations -- Explanations for Criminal Behavior -- Forensic Science -- Data, Methods and Statistics -- Police and Law Enforcement -- Psychology of Law -- Social Interventions and Prevention.